Influence of Al2O3 nanoparticle mass concentration and aerosol formation parameters on tool vibration during turning of Ti6Al4V titanium alloy - Dylewicz, Weronika; Szczotkarz, Natalia; Maruda, Radosław; Gupta, Munish Kumar (Zielona Góra: Uniwersytet Zielonogórski)
Machining difficult-to-cut materials involves challenging machining conditions, including higher temperatures in the cutting zone, cutting forces and friction. Another important phenomenon is vibration, which is undesirable when manufacturing high quality workpieces. One way to reduce vibration in the cutting zone is to use cooling methods. Due to its environmentally friendly nature, the minimum quantity lubrication (MQL) method has already been widely used in metalworking.
Keywords: Al2O3 nanoparticles; nanofluids; MQL; vibrations; variable air flow rate; variable nanofluid flow rate